What physical habitat factors determine the distribution of gastropods in neotropical headwater streams? - Marden S. Linares; Diego R. Macedo; Rodrigo L. Massara; Marcos Callisto (Water Biology and Security, 2022)
Freshwater gastropods play a pivotal role in the structure and functioning of freshwater ecosystems, but despite their importance, there are still gaps in their ecology. Our goal was to understand what physical habitat factors are the most important for the distribution of freshwater gastropods in headwater stream ecosystems in the Neotropical Savanna and provide a baseline for conservation and management efforts for freshwater gastropods in this biome. We identified five taxa, each with different environmental prefferences. Littoridina presence related negatively with stream slope, Biomphalaria presence related positively with total dissolved solids and the proportions of cobble, fine sediment and organic matter. Gundlachia presence correlated positively with elevation and the proportion of pools in the site. Physa presence related negatively with total dissolved solids and positively with alkalinity. Melanoides tuberculata presence correlated positively with the proportion of coarse gravel. Our results highlight the challenge for protecting native freshwater gastropod assemblages (and managing non-native invasive species), because environmental preferences vary widely amongst taxa and most are vulnerable to common anthropogenic disturbances.